Relapses Requiring Intravenous Steroid Use and Multiple-Sclerosis-related Hospitalizations: Integrated Analysis of the Delayed-release Dimethyl Fumarate Phase III Studies - Giovannoni, Gavin; Gold, Ralf; Fox, Robert J; Kappos, Ludwig; Kita, Mariko; Yang, Minhua; Sarda, Sujata P; Zhang, Ray; Viglietta, Vissia; Havrdova, Eva (Clinical therapeutics, 2015)
PURPOSE: The purpose was to report the effects of delayed-release dimethyl fumarate (DMF; also known as gastro-resistant DMF) on the number of relapses requiring intravenous (IV) steroids and multiple sclerosis (MS)-related hospitalizations using integrated data from the Phase III DEFINE and CONFIRM studies. METHODS: DEFINE and CONFIRM were randomized, double-blind, placebo-controlled, multicenter studies that evaluated the efficacy and safety of DMF over a 2-year period in patients with relapsing-remitting MS (RRMS). Patients were randomized (1:1:1) to receive oral DMF 240 mg BID or TID, placebo, or glatiramer acetate (CONFIRM only). Eligible subjects (aged 18-55 years) had an EDSS score of 0-5.0 and experienced either ≥1 relapse in the 12 months or had ≥1 gadolinium-enhanced lesion on brain MRI in the 6 weeks, before randomization. Data DEFINE and CONFIRM were pooled and analyzed using a negative binomial regression model (adjusted for study and region). Data obtained after subjects switched to an alternative MS therapy were not included in the analysis. Only relapses confirmed by the Independent Neurology Evaluation Committee were included in the analysis of relapses requiring IV steroids. FINDINGS: The study population (intention-to-treat) comprised 2301 patients who received either placebo (n = 771), DMF BID (n = 769), or DMF TID (n = 761). Baseline demographic and disease characteristics were generally well balanced among treatment groups. Throughout the 2-year studies, the total number of relapses treated with methylprednisolone was 402, 221, and 209 in the placebo, DMF BID, and DMF TID groups, respectively. A smaller proportion of patients in the DMF BID (168 of 769 [21.8%]) and DMF TID (151 of 761 [19.8%]) groups experienced ≥1 relapse requiring IV steroids compared with the placebo group (284 of 771 [36.8%]). The total number of MS-related hospitalizations over 2 years was 136, 94, and 74 in the placebo, DMF BID, and DMF TID groups. A smaller proportion of patients in the DMF BID (73 of 769 [9.5%]) and DMF TID (57 of 761 [7.5%]) groups had ≥1 MS-related hospitalization compared with the placebo group (104 of 771 [13.5%]). IMPLICATIONS: DMF is an effective and well tolerated therapy for RRMS. In addition to clinical benefits, the use of DMF may be associated with reduced patient burden and health economic savings, resulting from a decrease in resource utilization associated with relapses. ClinicalTrials.gov identifiers: NCT00420212 and NCT00451451.
Keywords: relapse; Magnetic Resonance Imaging; hospitalization; magnetická rezonanční tomografie; Humans; lidé středního věku; Delayed-Action Preparations; Dimethyl Fumarate; dimethyl fumarát; injekce intravenózní; Female; dospělí; lidé; methylprednisolone; hospitalizace; randomizované kontrolované studie jako téma; imunosupresiva; dimethyl fumarate; Adult; Immunosuppressive Agents; Glatiramer Acetate; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; methylprednisolon; Hospitalization; Male; Middle Aged; Randomized Controlled Trials as Topic; multiple sclerosis; léky s prodlouženým účinkem; Methylprednisolone; Injections, Intravenous; costs; glatiramer acetát; mužské pohlaví; Clinical Trials, Phase III as Topic; klinické zkoušky, fáze III jako téma